PERUBAHAN AKTA PERSEROAN TERBATAS OLEH NOTARIS DALAM RANGKA PENAWARAN UMUM (GO PUBLIC) - Yogi Agus Saputra (UNES Law Review, 2021)
Along with economic development, companies both small, medium and large scale always try to develop their business, one of which is how to meet capital needs. As for how to meet these capital needs by investing. Types and forms of investment are divided into two, namely: direct investment and indirect investment. Notary is one of the capital market supporting institutions where the notary is a general official who makes the deed of Amendment to the Articles of Association including Underwriting Agreement, Inter-Underwriter Agreement, Share Administration Management Agreement, Warrant Issuance Statement, Share Administration Management Agreement and other necessary agreements. To be able to carry out activities in the capital market sector, it must first be registered with the Financial Services Authority. The notary profession as one of the capital market supporting professions which will be the object of the author's research. The problems are: 1. How is the substance change in the Articles of Association of a Limited Liability Company in the context of a Public Offering (Go Public)? 2. What is the responsibility of the Notary on the deeds he made in the context of a public offering (going public)? The method used in this research is an empirical juridical approach, namely approaching the problem through research by looking at the norms or legal provisions that apply. Based on research results. The substance of the articles to be disposed of in the Articles of Association must be in line with the assisting regulations of the Capital Market Law, the Keauang Service Authority, and the regulations of the Indonesia Stock Exchange. The Capital Market Law requires Notaries to be accountable materially and formally for deeds made in the framework of a public offering (going public), for this reason the notary must conduct in-depth research (due ligence) before the deeds are drawn up.